Presence of eggs of Toxocara spp. and hookworms in a student environment in Rio Grande do Sul, Brazil Presença de ovos de Toxocara spp. e ancilostomatídeos em ambiente estudantil do Rio Grande do Sul, Brasil - Tiago Gallina; Maria Antonieta Machado Pereira da Silva; Luciana Laitano Dias de Castro; Emília Welter Wendt; Marcos Marreiro Villela; Maria Elisabeth Aires Berne (Revista Brasileira de Parasitologia Veterinária, 2011)
Environmental contamination by parasite forms was studied on a university campus in the municipality of Pelotas, Rio Grande do Sul. Soil samples were analyzed using the modified Caldwell & Caldwell technique to identify parasite forms. Nematode eggs were detected in 62% of the samples. Among the parasites detected, eggs of Toxocara spp. and Ancylostomatidae were the most prevalent parasites in the studied area throughout the study period. The results demonstrated that there is significant environmental contamination, thereby representing a risk of zoonotic infection for humans frequenting the study area. A contaminação ambiental por formas parasitárias foi estudada na área do campus universitário no município de Pelotas, Rio Grande do Sul. Amostras de solo foram analisadas para identificação de formas parasitárias e a presença de ovos de nematóides foi verificada em 62% das amostras. Entre os parasitos observados destacam-se a presença de ovos de Toxocara spp. e de ancilostomatídeos em todo período estudado. Os resultados demonstram que há contaminação ambiental significativa, o que representa risco de infecção zoonótica aos humanos que frequentam a região estudada.